Road conditions and engineering performance of subgrade soils in part of South-Western Nigeria (2014)
Studies on subgrade performance and failure of road pavement in parts of Southwestern Nigeria have been carried out. However, an enquiry on native subgrade soils which combines geotechnical data with drainage system in establishing causes of road failure is yet to be made. In a reconnaissance survey, major outcrops, stable and failed (unstable) portions of roads in Ago-Iwoye were identified. Disturbed and undisturbed samples of subgrade soils were obtained by hand auger and U-4 tubes respectively from 18 burrowed pits. Grading, consistency, specific gravity and strength properties of the soils were evaluated through the laboratory, British conventional procedures. For comparison at stable and failed (unstable) sections of the roads, subgrade soils at failed portions of the roads have higher clay (35%) and fines (11%) content with inconsistent plasticity characteristics compared to subgrade soils at stable portions. It is also observed that lower cohesive strength and unsoaked CBR apparently instigated failure of the roads pavements at Ago-Iwoye locality. In addition, the drainage system combined with soils’ moisture-density enhances road failure against the axial loading